Potential US Population Impact of the 2017 ACC/AHA High Blood Pressure Guideline - Muntner, Paul; Carey, Robert M; Gidding, Samuel; Jones, Daniel W; Taler, Sandra J; Wright, Jr, Jackson T; Whelton, Paul K (Circulation (New York, N.Y.), 2018)
The 2017 American College of Cardiology/American Heart Association (ACC/AHA) Guideline for the Prevention, Detection, Evaluation and Management of High Blood Pressure in Adults provides recommendations for the definition of hypertension, systolic and diastolic blood pressure (BP) thresholds for initiation of antihypertensive medication, and BP target goals. This study sought to determine the prevalence of hypertension, implications of recommendations for antihypertensive medication, and prevalence of BP above the treatment goal among US adults using criteria from the 2017 ACC/AHA guideline and the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC7). The authors analyzed data from the 2011 to 2014 National Health and Nutrition Examination Survey (N = 9 623). BP was measured 3 times following a standardized protocol and averaged. Results were weighted to produce US population estimates. According to the 2017 ACC/AHA and JNC7 guidelines, the crude prevalence of hypertension among US adults was 45.6% (95% confidence interval [CI]: 43.6% to 47.6%) and 31.9% (95% CI: 30.1% to 33.7%), respectively, and antihypertensive medication was recommended for 36.2% (95% CI: 34.2% to 38.2%) and 34.3% (95% CI: 32.5% to 36.2%) of US adults, respectively. Nonpharmacological intervention is advised for the 9.4% of US adults with hypertension who are not recommended for antihypertensive medication according to the 2017 ACC/AHA guideline. Among US adults taking antihypertensive medication, 53.4% (95% CI: 49.9% to 56.8%) and 39.0% (95% CI: 36.4% to 41.6%) had BP above the treatment goal according to the 2017 ACC/AHA and JNC7 guidelines, respectively. Compared with the JNC7 guideline, the 2017 ACC/AHA guideline results in a substantial increase in the prevalence of hypertension, a small increase in the percentage of US adults recommended for antihypertensive medication, and more intensive BP lowering for many adults taking antihypertensive medication.